2004
DOI: 10.1111/j.1464-410x.2004.04795.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet, anthropometric measures and prostate cancer risk: a review of prospective cohort and intervention studies

Abstract: We reviewed 37 prospective cohort and four intervention studies on potential dietary risk factors for prostate cancer, published between 1966 and September 2003. Some studies were limited by small size, crude measurement of dietary exposure and limited control for confounders. Intervention and prospective cohort studies support a protective role against prostate cancer for selenium, and possibly for vitamin E, pulses and tomatoes/lycopene. Overall consumption of meat, eggs, vegetables, fruit, coffee, tea, caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 72 publications
1
95
0
1
Order By: Relevance
“…Findings on fat, meat and prostate cancer have been recently reviewed, 4,41,42 and therefore the discussion here focuses on more recent additions to the literature, particularly results from prospective studies and reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Findings on fat, meat and prostate cancer have been recently reviewed, 4,41,42 and therefore the discussion here focuses on more recent additions to the literature, particularly results from prospective studies and reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Potential reasons for more aggressive prostate cancer among obese men include alterations in the balance of serum hormonal concentrations (estrogen, testosterone, insulin, and leptin; refs. [17][18][19], as well as dietary and lifestyle factors (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…23,20 For linoleic acid, the predominate omega-6 fatty acid in the Western diet, three of four studies showed no effect. 29 Two interventional pilot studies coupling a low-fat diet with supplementation with specific fatty acids deserve mention. In 2001, Demark-Wahnefried et al 30 published a small trial of 25 patients awaiting prostatectomy for prostate cancer placed on a diet (mean of 34 days), which was low in fat (20% of kilocalories or fewer) and supplemented with 30 mg/day of flaxseed, a compound rich in alpha-linolenic acid and lignans with phytoestrogenic properties.…”
Section: Dietary Fatmentioning
confidence: 99%